2019
DOI: 10.3390/ijms20235980
|View full text |Cite
|
Sign up to set email alerts
|

Onconase Restores Cytotoxicity in Dabrafenib-Resistant A375 Human Melanoma Cells and Affects Cell Migration, Invasion and Colony Formation Capability

Abstract: Melanoma is a lethal tumor because of its severe metastatic potential, and serine/threonine-protein kinase B-raf inhibitors (BRAFi) are used in patients harboring BRAF-mutation. Unfortunately, BRAFi induce resistance. Therefore, we tested the activity of onconase (ONC), a cytotoxic RNase variant, against BRAFi-resistant cells to re-establish the efficacy of the chemotherapy. To do so, an A375 dabrafenib-resistant (A375DR) melanoma cell subpopulation was selected and its behavior compared with that of parental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 54 publications
4
24
0
Order By: Relevance
“…Nevertheless, the use of a miR-17* mimic and a miR-30c inhibitor significantly decreased the ONC activity and the expression of NFKB1(p50) and its downstream targets [ 78 ]. This result is in agreement with other works that describe a decrease of NFKB1(p50) [ 69 ] and a downregulation in the steady state and subcellular distribution of NF-kappaB [ 66 , 79 , 80 ] as a result of ONC action on the treated cells.…”
Section: Regulatory Rnas Are Key Targets For Different Antitumor Rsupporting
confidence: 93%
“…Nevertheless, the use of a miR-17* mimic and a miR-30c inhibitor significantly decreased the ONC activity and the expression of NFKB1(p50) and its downstream targets [ 78 ]. This result is in agreement with other works that describe a decrease of NFKB1(p50) [ 69 ] and a downregulation in the steady state and subcellular distribution of NF-kappaB [ 66 , 79 , 80 ] as a result of ONC action on the treated cells.…”
Section: Regulatory Rnas Are Key Targets For Different Antitumor Rsupporting
confidence: 93%
“…Preliminary results (not shown) indicated the anti-tumor activity of the dimeric species suffers time latency, similarly to that exerted by ONC in A375 cell line [ 42 , 43 ]. Therefore, we report in Figure 6 A,B the data of cell viability assays measured with sulforhodamine B (SRB) sodium salt after 72 h cells incubation with all RNase A dimers.…”
Section: Resultsmentioning
confidence: 93%
“…Furthermore, these effects were particularly evident in the A375R cell line, which exhibited resistance to dabrafenib, a mutated BRAF inhibitor, which opens up a new perspective for PARP-i use in the case of resistant melanoma treatment [ 46 ]. Raineri et al showed that A375 cells treated with PARP1-i, AZD2461 in combination with onconase, a ribonuclease enzyme with strong antitumor activity in a number of cancers, inhibited the PARP1-NF-κB pathway, which resulted in reduced cell colony formation, migration, and invasion as well as elevated induction of apoptosis [ 47 , 48 ]. Moreover, another PARP-i, olaparib, although used as a monotherapy, does not exert any significantly therapeutic effect in uveal melanoma patients; however, when combined with dacarbazine, it increased its effectiveness [ 49 ].…”
Section: Discussionmentioning
confidence: 99%